2004
DOI: 10.1124/mol.65.2.370
|View full text |Cite
|
Sign up to set email alerts
|

Use-Dependent Inhibition of the N-Methyl-D-aspartate Currents by Felbamate: a Gating Modifier with Selective Binding to the Desensitized Channels

Abstract: Felbamate (FBM) is a potent nonsedative anticonvulsant whose clinical effect may be related to the inhibition of N-methyl-Daspartate (NMDA) currents, but the exact molecular action remains unclear. Using whole-cell patch-clamp recording in rat hippocampal neurons, we found that submillimolar FBM effectively modifies the gating process of NMDA channels. During a single high-concentration (1 mM) NMDA pulse, FBM significantly inhibits the late sustained current but not the early peak current. However, if the 1 mM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(57 citation statements)
references
References 28 publications
4
53
0
Order By: Relevance
“…Double-mutant cycle analysis of A652(NR1) and A651(NR2B) mutations consistent with the ideas that the foregoing residues are located in the external vestibule of the pore and are closely related to the activation gating control of the channel (see Introduction). In this regard, it is interesting to note that felbamate, the only approved anticonvulsant with significant gating-modification effects on NMDA receptors (Kuo et al, 2004), also binds to this region and acts as an "opportunistic" pore blocker with the "entrance" of its binding site undergoing a large gating conformational change Kuo, 2007a,b, 2008). Moreover, MT-SEA and MTSET modification of M3c (NR2B) is ϳ500-to 1000-fold faster in the activated than in the closed channels for the positions below A648 -A651 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Double-mutant cycle analysis of A652(NR1) and A651(NR2B) mutations consistent with the ideas that the foregoing residues are located in the external vestibule of the pore and are closely related to the activation gating control of the channel (see Introduction). In this regard, it is interesting to note that felbamate, the only approved anticonvulsant with significant gating-modification effects on NMDA receptors (Kuo et al, 2004), also binds to this region and acts as an "opportunistic" pore blocker with the "entrance" of its binding site undergoing a large gating conformational change Kuo, 2007a,b, 2008). Moreover, MT-SEA and MTSET modification of M3c (NR2B) is ϳ500-to 1000-fold faster in the activated than in the closed channels for the positions below A648 -A651 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…272,273 The drug acts as an allosteric modulator of channel gating, 274 with a preferential action to stabilize the inactivated state so as to produce a usedependent block. 275 This use-dependent action may selectively inhibit NMDA receptors that are excessively activated as is believed to occur during seizure discharges.…”
Section: Ionotropic Glutamate Receptorsmentioning
confidence: 99%
“…However, this effect appears to be specific for GABA A receptors containing α1 or α2 subunits along with β2 or β3 subunits (Simeone and McClellan, 2000). In addition, felbamate at a concentration of 100 μM has been found to block NMDA receptor mediated synaptic responses (Pugliese et al, 1996) and to inhibit NMDA receptor currents in isolated neurons (K d , ~1 mM; Rho et al, 1994;Subramaniam et al, 1995;Kuo et al, 2004). Studies with recombinant NMDA receptor subunit combinations have indicated that felbamate selectively bocks NMDA receptors composed of NR2B subunits at lower concentrations (IC 50 , 0.5 mM), than other subunit combinations Harty and Rogawski, 2000).…”
Section: Carbamates: Flurofelbamate and Rwj-333369mentioning
confidence: 99%